Historical Cultural Maritime Notes and the Integration of Its Values in Shaping the Self-Reliance of Coastal Ecotourism - Syahlan Mattiro; Cucu Widaty; Yuli Apriati (Yupa: Historical Studies Journal, 2023)
Until now, studies of Indonesian history have primarily concentrated on events that transpired on land, even though more than half of the territory of the Republic of Indonesia is composed of the sea. Such a dependency on the sea among many Indonesians indicates that a substantial portion of the past experiences and activities of the Archipelago's inhabitants has eluded the observation and research efforts of our nation's historians. This trend presents significant opportunities for the growth and development of Indonesian tourism. Indonesia, as the largest archipelagic country in the world, boasts rich biodiversity, a vast coastline of more than 81,000 km, and a total of 17,504 islands, among which 10,000 are classified as small islands, some of which remain unnamed and uninhabited. Mandar is one of the tribes in the archipelago that inhabits the coastal area of Kotabaru, South Kalimantan province, where the sea heavily influences its culture. The results of this study describe the potential for coastal tourism developed by the Mandar Community, which includes Pencak Silat, sea pandan handicrafts, and traditional sea alms ceremonies. The potential for tourism development is expected to transform these attractions into an economic catalyst for the local community in the area.